1986
DOI: 10.1111/j.1432-1033.1986.tb10461.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylamine oxidase from Arthrobacter P1. A bacterial copper-quinoprotein amine oxidase

Abstract: Methylamine oxidase from Arthrobacter P1 was purified to homogeneity. The enzyme oxidizes primary amines but not tyramine or polyamines like spermine and putrescine. The enzyme activity has a pH optimum of 8.0 with methylamine, and is inhibited by certain cations as well as anions at rather low concentrations. The enzyme has an M , of 167900, an isoelectric point of 4.6, consists of two (probably identical) subunits (Mr 82250) and contains two copper atoms but no sugar residues. The visible absorption spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Azide perturbs the NMRD of PPAO to a greater extent than that of the other amine oxidases examined, as indicated in Table I. This result is consistent with a previous report, which suggested that, at 25 °C, azide could displace at most approximately 50% of the coordinated water that contributed to solvent relaxation via rapid exchange.27 Our NMRD measurements were made at 5 °C, where previous results indicate that the binding of anions [Protein] = 0.05 mM in 50 mM KP04 (pH 7.0). Note: The actual copper content of the apo sample is 3% (0.06:1 = Cu(II):proteln).…”
Section: Resultssupporting
confidence: 91%
“…Azide perturbs the NMRD of PPAO to a greater extent than that of the other amine oxidases examined, as indicated in Table I. This result is consistent with a previous report, which suggested that, at 25 °C, azide could displace at most approximately 50% of the coordinated water that contributed to solvent relaxation via rapid exchange.27 Our NMRD measurements were made at 5 °C, where previous results indicate that the binding of anions [Protein] = 0.05 mM in 50 mM KP04 (pH 7.0). Note: The actual copper content of the apo sample is 3% (0.06:1 = Cu(II):proteln).…”
Section: Resultssupporting
confidence: 91%
“…The first bacterial one was methylamine oxidase from the grampositive bacterium Arthrobacter PI (van Iersel et al, 1986). Aromatic and aliphatic amine oxidases, probably of the quinoprotein type, have been detected in yeasts, and aromatic and aliphatic enzymes have been found in the same strains (Haywood and Large, 1981 ;Bruinenberg et al, 1989;Mu et al, 1992).…”
mentioning
confidence: 99%
“…In many Gram-negative methylotrophs, such as Methylobacterium extorquens AM1, MA is oxidized by a periplasmic methylamine dehydrogenase (MaDH) (8,9) to formaldehyde. Methylamine oxidase, a Cu-containing enzyme present in Gram-positive methylotrophs (10) and methylotrophic yeast strains (11), oxidizes MA to formaldehyde (12) in a single step as well. In contrast, the N-methylglutamate (NMG) pathway, originally described in Pseudomonas spp.…”
mentioning
confidence: 99%